How to attract foreign students - Arnaud Chevalier (IZA World of Labor, 2014)
To expand the skilled workforce, countries need to attract skilled migrants. One way of doing this is by attracting and retaining international students. Empirical evidence suggests that concerns about brain drain—that is, the emigration of highly qualified workers—are overblown and that student migration can positively affect economic growth in both sending and receiving countries. However, migrants themselves reap most of the gains, through higher earnings. So that in the end, international student mobility can be beneficial for all participants: migrating students and those who remain at home, as well as home and host societies.
Keywords: I23; I25; J61; 330; higher education; migration; study abroad